2021
DOI: 10.1097/brs.0000000000004221
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness and Functional Outcome of C2 Dome-like Expansive Versus C2 Expansive Open-door Laminoplasty for Upper Cervical Ossification of the Posterior Longitudinal Ligament

Abstract: This study performed an analysis of C2 dome-like expansive laminoplasty (Group Dom) and C2-7 expansive open-door laminoplasty (Group Exp). The space available for cord in Group Exp was significantly larger than Group Dom, while the visual analog scale score of Group Dom became significantly larger.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Therefore, they suspected that C2 single-door laminoplasty could not increase the incidence of postoperative cervical kyphosis. Yu et al ( 22 ) showed that there was no significant difference in the results of CCI at the last follow-up between the two groups of patients who underwent C2 single-door surgery or C2-DOM. In the present study, postoperative CCI in the C2-PL group was not significantly different from that in the C2-DOM group with less damage to the C2 muscle attachment, which could be related to the fact that the majority of patients in the C2-PL groups had continuous OPLL located behind the C2 and C3 vertebral bodies, and bony structure maintained the cervical lordosis, which could also be attributed to the small sample size of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they suspected that C2 single-door laminoplasty could not increase the incidence of postoperative cervical kyphosis. Yu et al ( 22 ) showed that there was no significant difference in the results of CCI at the last follow-up between the two groups of patients who underwent C2 single-door surgery or C2-DOM. In the present study, postoperative CCI in the C2-PL group was not significantly different from that in the C2-DOM group with less damage to the C2 muscle attachment, which could be related to the fact that the majority of patients in the C2-PL groups had continuous OPLL located behind the C2 and C3 vertebral bodies, and bony structure maintained the cervical lordosis, which could also be attributed to the small sample size of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Four trapezoidal homogeneous bone blocks were fixed to the C3–C6 bilateral spinous processes with double 10-gauge wire, and the knots were checked and firmly fixed. When faced with C2 decompression, we performed Dome-like Expansive LAMP ( 16 , 17 ) ( Figure 1 ). Briefly, a drill was applied to make a dome-like groove on the caudal surface of the C2, removed part of the anterior portion of the laminae, and then carefully excised the excess hypertrophic ligamentum flavum and part laminae.…”
Section: Methodsmentioning
confidence: 99%